Muadh's Hadith on Analogy Between the Ahl Al Hadith and The Osulion - Uthman M. Gharib; Ali Ahmad Mohammad (QALAAI ZANIST JOURNAL, 2022)
Praise be to God, Lord of the Worlds, and prayers and peace be upon the Master of the Messengers, our Prophet Muhammad and all his family and companions. Then: There is no doubt that the science of hadith and the science of jurisprudence are among the most important sciences in the life of a student of knowledge, for in the first place: distinguish correct hadith from bad, and in the second distinguish correct understanding from bad understanding, although there are many hadiths that are inferred by fundamentalists and jurists, and even have some important rules, and issues The subtleties need to be researched, scrutinized, and judged, because in their confirmation the soul is more assured of it, and in its weakness the inference from it is weakened. Among the most prominent of these hadiths that were inferred by the fundamentalists, as well as became famous and spread and filled the books of Sunnah - from the Sunan, Musnads, and compilations - and jurisprudence and assets: It is a hadith on the authority of Muadh bin Jabal: When the Prophet  wanted to send him to Yemen, he said to Adha? He said: I spend the book of God, he said, did not find in the Book of Allah ?, said: Vpsonh Messenger of Allah, peace be upon him, he said, it did not find in the Sunnah of the Messenger of Allah , nor in the Book of Allah? He said: Strive for my opinion and not a family, so the Messenger of God, may God’s prayers and peace be upon him, struck his chest and said: “Praise be to God, who is the Messenger of God.” Although the hadith scholars differed in correcting it and weakening it, the fundamentalists have often used it as evidence for the nation’s acceptance of it regardless of its chain of transmission. That is why we liked to collect the sayings of the scholars in this blessed hadith, asking the honorable Lord to bestow on us His kindness, and not to deprive us of His wisdom, and whoever is given wisdom has been given a lot of good.